Analysis Of Competencies, Work Discipline And Work Environment On Job Satisfaction At PT ISS Indonesia Medan Branch - Telaumbanua, Darman; Hasibuan, Hasrul Azwar (Universitas Dehasen Bengkulu, 2025)
This research was conducted with the aim of determining the influence of competence, work discipline and work environment on the job satisfaction of employees of PT. ISS Indonesia Medan Branch. The approach of this research uses quantitative and descriptive. Where seen from the type of data, this study uses a quantitative approach, but in terms of research explanation uses a descriptive approach. The population in this study is all employees of PT. ISS Indonesia Medan Branch which totals 46 people. The sample in this study uses a saturation or census technique where all members of the population are used as a sample of 46 employees. The author collected research data by distributing a questionnaire and then analyzed the data using multiple linear regression formulas, t-tests, f tests, and determination coefficients processed using the SPSS22 application. The results obtained from this study are (1) There is a significant influence between competence on employee satisfaction, (2) There is a significant influence between work discipline on employee satisfaction, (3) There is a significant influence between work environment on employee satisfaction, (4) There is a significant influence between competence, work discipline and work environment on employee satisfaction where the value of F-calculation (638,696) is greater than the F-table (2.59) with a probability of sig 0, 000 < 0.05. Meanwhile, based on the results of the determination coefficient, it shows (98.9%) which can be explained as the magnitude of the influence of the variables of competence, work discipline and work environment on employee satisfaction while the remaining 1.1% is found in variables outside the study.